Biochemistry and Semiconductor Electronics – The next Big Hit for Silicon? - Lindsay, Stuart (2012)
Two recent developments portend a new era for silicon electronics in biomedical applications. Firstly, highly specific chemical recognition and massively parallel sample preparation techniques are being combined with VLSI to make new kinds of analytical chips. Secondly, critical dimensions are beginning to approach the size of biomolecules, opening new pathways for physical interactions between molecules and semiconductor structures. Future generations of hybrid chemical-CMOS devices could revolutionize diagnosis and make personalized medicine cheap enough to become widespread.